2015
DOI: 10.2147/ijn.s82486
|View full text |Cite
|
Sign up to set email alerts
|

Sustained release of VH and rhBMP-2 from nanoporous magnesium–zinc–silicon xerogels for osteomyelitis treatment and bone repair

Abstract: Nanoporous magnesium–zinc–silicon (n-MZS) xerogels with a pore size ∼4 nm, a surface area of 718 cm 2 /g, and a pore volume of 1.24 cm 3 /g were synthesized by a sol–gel method. The n-MZS xerogels had high capacity to load vancomycin hydrochloride (VH) and human bone morphogenetic protein-2 (rhBMP-2), after soaking in phosphate buffered saline (PBS) for 24 hours (1.5 and 0.8 mg/g, respectively). Moreover, the n-MZS xerogels exhibited the sustained release of VH and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 39 publications
0
4
0
3
Order By: Relevance
“…(ii) control of appropriate release rates upon tissue. (iii) the potentially targeted drug delivery to specific cells, and (iv) the preservation of drug functionality and integrity during construction of the scaffold 5,6 . So far little studies reported how the spatiotemporal control of drug may affect tissue repair.…”
Section: Introductionmentioning
confidence: 99%
“…(ii) control of appropriate release rates upon tissue. (iii) the potentially targeted drug delivery to specific cells, and (iv) the preservation of drug functionality and integrity during construction of the scaffold 5,6 . So far little studies reported how the spatiotemporal control of drug may affect tissue repair.…”
Section: Introductionmentioning
confidence: 99%
“…In the drug delivery system with nanoporous magnesium–zinc–silicon as the carrier, the co-release profile of BMP-2 and vancomycin is not significantly different from that of the two drugs alone, which proves that vancomycin and BMP-2 have no mutual influence on drug diffusion and release ( Fig. 8 ) [ 188 ]. Moreover, vancomycin and the BMP-2 double-drug-loaded silicon-imprinted calcium phosphate scaffold and BMP-2 single-drug-loaded silicon-imprinted calcium phosphate scaffold both significantly promote new bone formation of rat tibial defects.…”
Section: Dual-functional Drug Delivery Systemmentioning
confidence: 99%
“…Постепенная (в течение семи месяцев) метаболизация металлических фиксаторов из биодеградирующего магниевого сплава МЛ-10 организмом белых беспородных крыс-самцов сопровождалась отсутствием нарушений физиологических проявлений. Исходя из результатов эксперимента, можно рекомендовать металлические фиксаторы из биодеградирующего магниевого сплава МЛ-10 для применения у человека [6,15].…”
Section: результаты и их обсуждениеunclassified
“…Поиск оптимальных материалов для остеосинтеза продолжается. Неоднократно исследователи обращали внимание на магний и его сплавы, одним из свойств которых является растворимость в водной среде [6].…”
Section: Introductionunclassified
See 1 more Smart Citation